Pore structure and fractal characteristics of deep shale gas reservoirs in the Western Chongqing block, Sichuan Basin - Feifei Fang; Sijie He; Jie Zhang; Xizhe Li; Hua Zhang; Yan Chang; Xin Li (PLoS ONE, 2026)
To date, researchers have not systematically investigated the geological characteristics of deep shale gas reservoirs in the Western Chongqing Block. Furthermore, the single technique remains insufficient for characterizing the complexity of their multi-scale pore structures. Therefore, this study integrates scanning electron microscopy (SEM), argon ion polishing-field emission scanning electron microscopy (AIP-FESEM), high-pressure mercury intrusion (HPMI), and low-pressure gas adsorption (LPGA) to qualitatively and quantitatively investigate the microscopic pore structure of shale gas reservoirs in the Western Chongqing block. Meanwhile, the pore fractal characteristics were analyzed based on HPMI and LPGA experiments using the mercury saturation model, the Frenkel-Halsey-Hill (FHH) model, and the volume-surface area (V-S) model. The results show that, first, the pore types of the samples in the Western Chongqing block include organic pores, intergranular pores, intragranular pores, intercrystalline pores, and interlayer fractures; second, micropores are the main contributors to the total pore volume, mainly developed in the three ranges of 0.45 ~ 0.5 nm, 0.55 ~ 0.6 nm, and 0.8 ~ 0.85 nm, followed by mesopores and finally macropores; finally, the macropores of the samples exhibit stronger heterogeneity and more complex pore-throat structures compared to mesopores. The heterogeneity of the pore structure is stronger than that of the pore surface, indicating a more complex internal pore structure. Additionally, the microporous structures of the samples are also characterized by relatively complex. The experimental results provide important guidance for the economical and efficient development of shale gas.